Hypolithic and soil microbial community assembly along an aridity gradient in the Namib Desert - Stomeo, Francesca; Valverde, A.; Pointing, S.B.; McKay, C.P.; Warren-Rhodes, K.A.; Tuffin, M.I.; Seely, M.; Cowan, D.A. (Springer, 2013)
The Namib Desert is considered the oldest desert in the world and hyperarid for the last 5 million years. However, the environmental buffering provided by quartz and other translucent rocks supports extensive hypolithic microbial communities. In this study, open soil and hypolithic microbial communities have been investigated along an East–West transect characterized by an inverse fog-rainfall gradient. Multivariate analysis showed that structurally different microbial communities occur in soil and in hypolithic zones. Using variation partitioning, we found that hypolithic communities exhibited a fog-related distribution as indicated by the significant East–West clustering. Sodium content was also an important environmental factor affecting the composition of both soil and hypolithic microbial communities. Finally, although null models for patterns in microbial communities were not supported by experimental data, the amount of unexplained variation (68–97 %) suggests that stochastic processes also play a role in the assembly of such communities in the Namib Desert.